Environmental Influence of Altitude on Coffee Leaf Rust Severity in Arabica Coffee of Aceh Tengah, Indonesia - Teguh Arkadinata; Qalbin Salim Fazli; Alfizar Alfizar; Lukman Hakim; Ghazi Mauer Idroes (Leuser Journal of Environmental Studies, 2025)
Coffee leaf rust (CLR), caused by Hemileia vastatrix, remains one of the most damaging diseases affecting Arabica coffee worldwide. Understanding how environmental gradients influence CLR development is critical for sustainable management in tropical highland systems. This study examined the influence of altitude on CLR incidence and severity across five elevation ranges (800–1800 masl) in Arabica coffee plantations of Aceh Tengah, Indonesia. Field assessments were conducted on 25 farms using a standardized sampling layout and severity scoring scale. Analysis of variance (ANOVA) revealed that altitude had no significant effect on disease incidence (F = 0.14 < F0.05 = 3.01), which remained uniformly high across all sites (>75%), but significantly affected disease severity (F = 3.34 > F0.05 = 3.01). The highest mean severity (51.88%) occurred at 1600–1800 masl, differing significantly from lower elevations. These findings suggest that while CLR infection frequency is widespread, environmental conditions at higher altitudes favor greater lesion expansion and disease development. The results highlight the importance of considering local microclimatic variability in disease risk assessment and adaptive management. Further studies integrating microclimatic and agronomic measurements are needed to strengthen causal understanding and support environmentally based strategies for sustainable Arabica coffee production.